1991
DOI: 10.1289/ehp.919333
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-ras transforming genes in chemical carcinogenesis.

Abstract: DNA transfection experiments using the NIH 3T3 mouse fibroblast cell line have demonstrated that chemically induced tumors and chemically transformed cell lines frequently contain dominant transforming genes. Although many of the genes detected using the NIH 3T3 transfection-transformation assay are activated versions of H-ras, K-ras, and N-ras, in some experimental systems activated forms of genes such as met and neu that are unrelated to ras have been observed. The activated met gene was originally detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Another example is the development of nervous system tumours in mice following transplacental exposure to N-ethyl-N-nitrosourea in which the activated NEU gene was detected. This gene normally encodes a novel growth factor receptor and its activation involves a single point mutation (Cooper, 1991). Human studies of cord blood T lymphocytes from newborns following transplacental exposure to cigarette smoke, albeit passive, revealed an increased rate of mutations (deletions) in those infants of exposed mothers (Finette et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Another example is the development of nervous system tumours in mice following transplacental exposure to N-ethyl-N-nitrosourea in which the activated NEU gene was detected. This gene normally encodes a novel growth factor receptor and its activation involves a single point mutation (Cooper, 1991). Human studies of cord blood T lymphocytes from newborns following transplacental exposure to cigarette smoke, albeit passive, revealed an increased rate of mutations (deletions) in those infants of exposed mothers (Finette et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The Mo-SV-specific sequence, later named mos , was found to have originated from the mouse genome and to be present in the human genome as well [67]. However, the incidence of mos mutations was low in human cancer cells, while enhanced expression was observed [68]. It was reported that mos kinase activated ERK in the Ras-Raf pathway [69].…”
Section: Timeline View: the “Oncogene Theory ” The Discovery Of Viramentioning
confidence: 99%